Playgrounds for learning, playgrounds for taking care (Journal of Parents and Teachers, 2014)
This article offers ideas for schoolyards to become safe and stimulating places for the education of students. In addition, it includes the experience of a school in Segovia in which the patio became the perfect setting to play a play, play traditional games and make a market.
Keywords: school playground; stimulating surrounding; ideas; Segovia.